ANALISIS PROSES DAN FINANSIAL INDUSTRI KECIL MIE PANGSIT WAHYU AGUNG JAYA MALANG - Wahyu Mushollaeni (Universitas Tribhuwana Tunggadewi, 2008)
The aims of this research were to elucidate the process and financial aspect of making boiled noodles in small scale industry Wahyu Agung Jaya Malang. Data was collected through observation and interview. Materials used for making boiled noodles were flour, tapioca, water and NaCl. The processes were mixing, pressing, dividing, boiling, cutting, drying, cooling and packing. The factory has a standard to controlling the process to produce good quality of product. Sanitation was applied in facilities, machines, employess and other facilities. NPV, IRR and PBP values were 69.261.988,98.; 0,41 or 41%; and 3 years and 4 months. Production capacity were 360 kg noodles/day